Effects of the COVID-19 pandemic on the mental health of seafarers: A comparison using matched samples - Pauksztat, B.; Andrei, Daniela; Grech, M.R. (ELSEVIER, 2022)
The COVID-19 pandemic and the measures implemented to curb its transmission have altered workplaces and challenged occupational health and safety in unprecedented ways, with high levels of mental distress reported across several industries. In the maritime industry, occupational health and safety risks, including psychosocial risks, were a concern already before the COVID-19 pandemic. However, knowledge about the prevalence of mental health problems and the factors associated with them is still limited. The purpose of this study was to investigate the impact of the COVID-19 pandemic as well as the effects of respondent and work-related characteristics on seafarers’ self-reported symptoms of depression and anxiety. Data came from two cross-sectional convenience samples of seafarers on international commercial vessels, surveyed before (Npre-pandemic = 793) and during the pandemic (Npandemic = 504). Matching the two samples on respondent and work-related characteristics using propensity scores, we found that the pandemic contributed to significantly higher levels of depression and anxiety. Further analyses showed that seafarers with longer work periods, those who had been on board longer than expected, and those working on vessels registered with “Flags of Convenience” reported significantly higher levels of both depression and anxiety during the pandemic, but not prior to the pandemic. Taken together, these findings suggest that the impact of the COVID-19 pandemic led to a deterioration of working conditions and increased mental health risks for seafarers. Practical implications for safe-guarding occupational health and safety during this and future crises are discussed.